2004
DOI: 10.1074/jbc.m401037200
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium-induced Calpain Mediates Apoptosis via Caspase-3 in a Mouse Photoreceptor Cell Line

Abstract: The rd mouse, an accepted animal model for photoreceptor degeneration in retinitis pigmentosa, has a recessive mutation for the gene encoding the ␤-subunit of the cGMP phosphodiesterase. This mutation results in high levels of cGMP, which leaves an increased number of the cGMP-gated channels in the open state, thus allowing intracellular calcium (Ca 2؉ ) to rise to toxic levels, and rapid photoreceptor degeneration follows. To delineate the events in rd photoreceptor degeneration, we demonstrated an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(59 citation statements)
references
References 25 publications
5
54
0
Order By: Relevance
“…The stressors generated by the effects of the gene mutation in the rd1 photoreceptor, calcium and oxidant stress, have been shown to result in mitochondria-dependent cell death (Sharma and Rohrer 2004, 2007). To examine whether short-term calcium or oxidant stress results in changes in mitochondrial reserve capacity, the 661W cells were exposed to calcium ionophore, A23187 (500 nM), or the oxidant, tBuOOH (50 µM), on the XF24 instrument for 30 min, after which the treated cells were exposed to FCCP (1 µM) to uncouple the mitochondrial membrane potential and thereby estimate mitochondrial reserve capacity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stressors generated by the effects of the gene mutation in the rd1 photoreceptor, calcium and oxidant stress, have been shown to result in mitochondria-dependent cell death (Sharma and Rohrer 2004, 2007). To examine whether short-term calcium or oxidant stress results in changes in mitochondrial reserve capacity, the 661W cells were exposed to calcium ionophore, A23187 (500 nM), or the oxidant, tBuOOH (50 µM), on the XF24 instrument for 30 min, after which the treated cells were exposed to FCCP (1 µM) to uncouple the mitochondrial membrane potential and thereby estimate mitochondrial reserve capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Sustained, increased levels of intracellular calcium also cause mitochondrial stress due to activation of ETC flux, and mitochondrial swelling (Yoshida et al 1992). Eventually, elevated calcium leads to mitochondrial failure and apoptosis as has been shown in the rd1 model of retinitis pigmentosa (RP) (Fox et al 1999; Sharma and Rohrer 2004) as well as other neurodegenerative diseases (Zglinicki 2003) and perhaps aging (Beckman and Ames 1998; Brand 2000; Brand and Nicholls 2011). Loss of mitochondrial reserve capacity in response to elevated ROS levels has also been demonstrated with the Seahorse Biosciences extracellular flux instrument in cellular models of renal, cardiovascular, and neurodegenerative diseases (Dranka et al 2010, 2011), as well as in MERRF syndrome using isolated skin fibroblasts (Wu and Wei 2012).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Refs. 12-15), immunohistochemical analyses have been performed to describe changes in protein expression in the rd/rd retina (16,17), and calcium-induced cell death in a photoreceptor culture model has been studied to unravel the apoptotic pathway (64). However, a clear picture has yet to emerge that describes the apoptotic pathways involved in photoreceptor degeneration in the rd/rd mouse.…”
mentioning
confidence: 99%
“…To further confirm the role of calcium in the activation of CaMKIV by Group I mGluRs, we then tested the effect of raising intracellular Ca 2ϩ by application of calcium ionophore A23187 (54,55)in ACC slices. We found that application of calcium ionophore A23187 (5 M, 15 min, and 30 min) could induce the phosphorylation of CaMKIV in ACC slices (169 Ϯ 8 and 157 Ϯ 9% of the control levels for A23187 at 15 and 30 min, respectively; p Ͻ 0.01, compared with control, n ϭ 4, Fig.…”
Section: Activation Of Camkiv By Group I Mglurs In the Accmentioning
confidence: 99%